Generative Artificial Intelligence in Agile Product Management: Optimizing Task Coordination and Team Efficiency in Software Development - Anissa Putri Widodo, Della; Voutama, Apriade Voutama (AI Society & STMIK Indonesia, 2025)
The inclusion of Artificial Intelligence (AI) into Agile Product Management is revolutionizing the process of efficient software development in terms of improved coordination of tasks and team productivity optimization. Though Agile processes have gained much momentum with their iterative approach, issues like ineffective backlog management, inefficient resource allocation, and lengthy sprints continue to persist with human errors and long-time product development that could be mitigated with the use of Generative AI. This study discusses how AI-driven automation can resolve such inefficiencies in the form of a case study of the MSIB Batch 7 2024 PINTURA project, where lead times in software development were cut from 6-12 months to just under 2 months.